Remoção de manganês de drenagem ácida de mina utilizando carvão de osso - Dalila Chaves Sicupira (2012)
Batch and continuous fixed bed tests were carried out aiming to evaluate the feasibility of using bone char for the removal of manganese from acid mine drainage (AMD). Tests with laboratory solution containing solely manganese at typical concentration levels were also carried out for comparison purposes. Equilibrium tests revealed that Langmuir based maximum manganese uptake capacity was 22 mg g-1 for AMD effluent and 20 mg g-1 for laboratory solution. Manganese kinetics onto bone char was best described by the pseudo-second order model. Manganese removal was influenced by operating variables solid/liquid ratio and pH of the aqueous phase, and it was favored at nearly neutral pH values. The effect of particle size and temperature was not significant for the operating range investigated. It has been found that intraparticle diffusion is the main rate-limiting step for manganese sorption systems but additional contribution from boundary layer diffusion might also affect removal when bone char particles of smaller sizes are used. The following operating variables were evaluated for continuous fixed bed tests: mass of bone char, flow rate and initial pH. Significant variations in resistance to the mass transfer of manganese into the bone char were identified using the Thomas model. A significant effect of bed height was observed only in tests with laboratory solution. No significant change on the breakthrough volume was observed with different flow rate. Increasing the initial pH from 2.96 to 5.50, the breakthrough volume was increased. The maximum manganese loading capacity calculated in continuous tests using bone char for AMD effluent was 6.03 mg g-1 and for laboratory solution was 26.74 mg g-1. The study included also desorption tests using solutions of HCl, H2SO4 and water but no promising results were obtained due to low desorption levels along with relatively high mass loss. Despite of this, the removal of manganese from AMD effluents using bone char as adsorbent is technically feasible thus attending environmental legislation. It is interesting to note that the use of bone char for manganese removal may avoid the need for pH correction of the effluent after treatment with lime. Also, it can remove fluoride ions and other metals, so bone char is a quite interesting alternative material for the treatment of AMD effluents.